Single-Crystal Diamond Nanowires Embedded with Platinum Nanoparticles for High-Temperature Solar-Blind Photodetector - Jiaqi Lu; Xinglai Zhang; Shun Feng; Bing Yang; Ming Huang; Yubin Guo; Lingyue Weng; Nan Huang; Lusheng Liu; Xin Jiang; Dongming Sun; Huiming Cheng (Nano-Micro Letters)
Highlights Single-crystalline diamond nanowires embedded with platinum nanoparticles were fabricated for high-temperature solar-blind photodetection. At room temperature, the photodetector's responsivity represents a 2000-fold enhancement compared to bulk diamond. At 275 °C, the device demonstrates a responsivity of 3098.7 A W-1, while maintaining excellent spectral selectivity. Multiple factors synergistically enhance performance, including one-dimensional carrier transport channels, deep-level defects, localized surface plasmon resonance effect, and localized Schottky junctions.